Convergent synthesis of tetrahydropyranyl side chain of verucopeptin, an antitumor antibiotic active against multidrug-resistant cancers. Issue 97 (9th November 2022) - Sun, Yuanjun; Tang, Wenhao; Ni, Huxin; Wang, Mei; Huang, Bin; Long, Ya-Qiu
Abstract : A concise synthesis of the tetrahydropyranyl side chain of verucopeptin, an antitumor antibiotic cyclodepsipeptide efficacious against multidrug-resistant cancer in vivo, is achieved using 12 steps in the longest linear sequence. Abstract : A concise synthesis of the tetrahydropyranyl side chain of verucopeptin, an antitumor antibiotic cyclodepsipeptide efficacious against MDR cancers in vivo, is achieved using 12 steps in the longest linear sequence and 21 total steps, in which Julia–Kocienski olefination for the segments coupling, asymmetric hydroxylation as well as stereoselective synthesis of stable tetrahydropyran ring from a d -isoascorbic acid derivative are key steps. This convergent synthetic strategy enables the structural modification and mechanism study of verucopeptin for its clinical applications.